Eksplorasi Dimensi Moralitas Remaja di Indonesia - Purwati Purwati; Muhammad Japar; Laily Qomariyah (Bulletin of Counseling and Psychotherapy, 2022)
Moral reasoning is very important for Indonesian teenagers to have. Adolescents who understand morals will have an impact on correct behavior and avoid deviant behavior. This is supported by the ability of adolescents to think logically in determining right or wrong decisions before taking action or speaking because it is the result of considering the basic values ​​of the norms they have. The research entitled "Exploring the Dimensionality of Adolescence's Moral in Indonesia" aims to find out how the morals of Indonesian youth today are. Exploration of a phenomenon or study in this research is carried out using the grounded theory method. The object of this research is the morals of teenagers in Indonesia. Data collection was carried out in two stages, namely Focus Group Discussion (FGD) and interviews. The FGD was carried out in four stages, two of which were conducted in Magelang City and the other two stages were conducted in Pekalongan City. The first FGD was conducted with 9 participants from counseling guidance (BK) teachers at the Junior High School Magelang City. The second stage was a FGD with 11 participants from religion teachers at the Junior High School Magelang City. The third stage of the FGD was conducted with six students from SMP as participants. And the last FGD was carried out with 9 participants from BK teachers in Junior High School in Pekalongan City. The following is. question guide used in the FGD. The results showed that morals have 4 dimensions, namely individual differences, belief, social, and value.